PENGEMBANGAN MEDIA FLASHCARD BERBASIS AUGMENTED REALITY PADA MATERI BANGUN RUANG UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF SISWA KELAS V SEKOLAH DASAR - Dian Ratna Sari; Hidayanto, Erry; Mashfufah, Aynin (Universitas Pendidikan Ganesha, 2023)
The lack of use of media in the process of learning mathematics then has an impact on the low cognitive ability of students, so to overcome these problems, students need media that can help the learning process. The purpose of this study is to produce flashcard media products based on augmented reality as a valid, practical, and effective media to improve students' cognitive learning outcomes. This research belongs to the type of development research that was developed using the ADDIE model with the stages of analysis, design, development, implementation, and evaluation. The subjects involved in this study were validators, teachers, and fifth grade elementary school students. Data collection was carried out using observation, interviews, questionnaires, and tests. The data collection instrument uses a questionnaire and test questions. Data analysis techniques used were descriptive analysis of qualitative, quantitative, and t-tests. The results of the analysis show that the validation of material experts obtained a percentage of 79.2%, which is included in the valid criteria. The second criterion, which is practical, was obtained through the teacher questionnaire and small group trial. Students obtained a percentage of 88.7% included in the very practical criteria, and the student questionnaire obtained a percentage of 89.5% included in the very practical criteria. The teacher and student questionnaires during the large group trial for teachers obtained a percentage of 91.2% included in very practical criteria and for students obtained a percentage of 88.3% included in very practical criteria. The third criterion is effectiveness. Based on these results, it can be concluded that flashcard media based on augmented reality can significantly improve students' cognitive abilities.